Review of the effect of biphosphonates on jaw osteonecrosis - Afshin Tahmasebi; Zahra Saberi; Farimah Sardari; Farzaneh Ashrafi; Parichehr Ghalyani (Isfahan University of Medical Sciences, 2011)
Introduction: Biphosphonates are used in the treatment of bone metastatic tumors and osteoporosis. The most adverse effect of bisphosphonates is osteonecrosis of jaws, which is difficult to control. The aim of this review was to evaluate articles published on the effect of these medications on jaws and methods to control and prevent its side effects in comparison with complications of radiotherapy in the head and neck region.Review report: A Pubmed/Medline search was run using the key words biphosphonates, osteonecrosis and jaws from 1980 to 2010. Of the 160 articles in the search results 44 were case reports.Results: Osteonecrosis of the jaws, with signs and symptoms similar to osteoradionecrosis, is a complication of biphosponate use, especially when used intravenously. Oral use of these medications is not absolutely contraindicated in dentistry.Conclusion: The best way to treat jaw necrosis is its prevention. There is a low risk for the incidence of osteonecrosis during the first 6 months of treatment with biphosphonates. Use of chlorhexidine mouthwash might be useful in these patients. Key words: Bisphosphonate, Jaw, Osteonecrosis, Osteoradionecrosis.